3D distribution of particulate organic carbon induced by the great whirl - Zha, Chenchen; Wang, Sen; Ying, Shiyao; Chen, Hui; Han, Guoqing (Frontiers in Marine Science, 2025)
Mesoscale eddies can affect the distribution of matter in the ocean due to their inherent characteristics, thereby affecting local ecosystems. However, there are few previous studies on the influence of Great Whirl (GW) on the distribution of particulate organic carbon (POC). This study analyzes the influence of the GW on the three-dimensional distribution of marine POC concentration in the northwestern Indian Ocean, off the coast of Somalia. It is shown that there are significant differences in the spatial distribution modes of POC in the surface and subsurface ocean of GW. In the sea surface, the POC concentration at the edge of GW is higher than the eddy center resulting from the capturing and transporting effect of GW. The difference is about 20 mg·m−3 between the center and the edge. At the subsurface layer (approximately between 50 and 175 m), the concentration of POC in the eddy center is high, while that in the surrounding water is low. The maximum difference between the center and the edge can reach about 10 mg·m−3. These phenomena show that GW will have an impact on the distribution of POC in the ocean, which in turn may affect the carbon cycle progress in the local ocean.